Implementing liberal management education through the lens of the other - ESTAD, Thomas (Institutional Knowledge at Singapore Management University, 2014)
The purpose of this paper is to explore the prerequisite conditions for implementing a liberal management education and for fostering ethical students using examples from the core curriculum at Singapore Management University (SMU). Beginning with a reading of the Carnegie Foundation's Rethinking Undergraduate Business Education: liberal learning for the professions (2011), the paper examines the contribution and limits of the findings and recommendations before discussing the place of the liberal arts in the modern university and describing a case study of liberal management education in process at SMU. It concludes with a reading of the work of Emmanuel Levinas and Asian philosophy as the basis for an ethical management education. The paper uncovers a central shortcoming in an otherwise important Carnegie study: that business education is unlike other professional education because it lacks an autonomous discipline that studies business knowledge production as an object. Consequently, applying the liberal arts to business education risks neglecting the critical side of the liberal arts. With only the reflective side of the liberal arts in operation, management education cannot be grasped as a specific sphere of values within the pluralism of spheres advocated by the Carnegie report. Only by recreating the function of an autonomous discipline with an objective lens on business knowledge within the core curriculum at SMU can that university attempt to incorporate both the critical and reflective side of the liberal arts in management education. This kind of liberal management education can indeed lead to respect for the values of the others in the way that ethical philosopher Emmanuel Levinas envisioned. Further development of the SMU core curriculum is necessary in order to confirm the hypothesis that the liberal arts can be brought together with management education to produce more mature, ethical students. Liberal management education curriculum must incorporate the critical function of the liberal arts when faced with business knowledge production in order to promote a pluralist ethics. If SMU is successful, it can become a model for other global business schools in Asia and beyond. Asian higher education is ongoing a rapid transformation in values. The shift is towards understanding the wider relationship between universities and society and the role of an education citizenry. Liberal management education can be a bridge to this new world of higher education in Asia, and beyond. This discussion provides a fuller understanding of the two-sided nature of the liberal arts and the importance of both sides for building a liberal management education and creating ethically mature students.